The Role of Artificial Intelligence in Empowering Women in Educational Systems: A Case Study of the Online University - Marzia Ebrahimi; Shafiqa Popalzay; Nazbu Azamy; Sabrina Karimi; Tamanna Quraishi (International Journal of Global Sustainable Research, 2025)
This study examines how Artificial Intelligence (AI) empowers female students within online educational systems, particularly in developing contexts. With the growth of e-learning, AI offers transformative opportunities to enhance educational access, engagement, and overcome traditional barriers. A cross-sectional survey was conducted with 110 female students from medical, computer science, education, and economics disciplines. Data were gathered through Likert scale and open-ended questions, focusing on AI use, learning experiences, and adoption barriers. Descriptive statistics analyzed the results, revealing that AI significantly enhances educational access and motivation among female students. However, technical issues and cultural constraints remain major challenges. The study concludes that while AI has strong potential to empower women in education, addressing these barriers is essential for wider, equitable adoption